Thrombospondin-1 (TSP-1) Analogs ABT-510 and ABT- 898 Inhibit Prolactinoma Growth and Recover Active Pituitary Transforming Growth Factor-b1 (TGF-b1) - Recouvreux, Maria Victoria (2012)
Prolactinomas are the most prevalent type of secreting pituitary tumors in humans and generally respond well to a medical therapy with dopamine agonists. However, for patients exhibiting resistance to dopaminergic drugs, alternative treatments are desired. Antiangiogenic strategies might represent a potential therapy for these tumors. Thrombospondin 1 (TSP-1) is a large multifunctional glycoprotein involved in multiple biological processes including angiogenesis, apoptosis, and activation of TGF- 1. Because tumors that overexpress TSP-1 grow more slowly, have fewer metastases, and have decreased angiogenesis, TSP-1 provides a novel target for cancer treatment. ABT-510 and ABT-898 are TSP-1 synthetic analogs that mimic its antiangiogenic action. In the present study, we explored the potential effect of ABT-510 and ABT-898 on experimental prolactinomas induced by chronic diethylstilbestrol (DES) treatment in female rats. We demonstrated that a 2-wk treatment with ABT-510 and ABT-898 counteracted the increase in pituitary size and serum prolactin levels as well as the pituitary proliferation rate induced by DES. These inhibitory effects on tumor growth could be mediated by the antiangiogenic properties of the drugs. We also demonstrated that ABT-510 and ABT-898, in addition to their described antiangiogenic effects, increased active TGF- 1 level in the tumors. We postulate that the recovery of the local cytokine activation participates in the inhibition of lactotrope function. These results place these synthetic TSP-1 analogs as potential alternative or complementary treatments in dopamine agonist-resistant prolactinomas.